Outsourcing the information technology function: Perspectives from employees - M. Sadiq Sohail (South African Journal of Business Management, 2012)
The purpose of this paper is to investigate human aspects of outsourcing and its impact on employees and organizational performance. This study is based on a questionnaire survey conducted in Saudi Arabia. Based on an extensive review of literature, the paper uses empirical research to analyse employees' attitude towards outsourcing. Results based on the analysis of data from 178 firms in Saudi Arabia indicate that employees largely perceive outsourcing as a positive development. Limitations of this paper relate to the relatively small size of the sample. Findings have several practical implications for small start-up firms and even larger firms that are deciding to outsource IT function in the Arabian Gulf region. The results provide managers with evidence supporting the benefits of IT outsourcing. This paper makes a valuable contribution given the fact that there are only a limited number of comprehensive studies dealing with the assessment of employees' attitude towards outsourcing IT functions. Most previous studies have looked into business aspects of outsourcing in IT function.
Keywords: 650